Composite deoxidation slag former for improving purity of bearing steel in vacuum process

By using a composite deoxygenation slag-making agent of metal aluminum wire, premelted refined slag and high-purity silicon carbide during vacuum degassing process, the problem that the existing technology cannot effectively improve the purity of bearing steel is solved, and the oxygen content in the molten steel is achieved The significant reduction in the size of the inclusions has improved the quality of the bearing steel.

CN119193989APending Publication Date: 2024-12-27NANJING IRON & STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411135837.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing slag-making agent cannot effectively improve the purity of bearing steel during the smelting process, especially after the smelting time is extended, the adsorption capacity of the refined slag will decrease, which cannot further improve the purity of the molten steel.

Method used

Using a composite deoxygenation slag-making agent, its main components include metal aluminum wire, pre-melted refined slag and high-purity silicon carbide, the oxygen content in the steel is reduced during vacuum degassing process and the adsorption of pre-melted refined slag Al2O3 inclusions improve the purity of the liquid steel.

Benefits of technology

Through this method, the oxygen content and inclusion size in the steel liquid are significantly reduced, the inclusion form changes from chain-shaped to granular, and the size is reduced from 38.28μm to 3~5.5μm, which significantly improves the purity of the bearing steel .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a composite deoxidation slag former for improving the purity of bearing steel in a vacuum process, the composite deoxidation slag former comprises the following main components in percentage by weight: 10-12% of metal aluminum wires, 63-70% of pre-melted refining slag and 20-25% of high-purity silicon carbide, the composite deoxidation slag former takes the pre-melted refining slag as a main body, 10-12% of the metal aluminum wires and 20-25% of the high-purity silicon carbide are added, and the pre-melted refining slag and the high-purity silicon carbide are uniformly mixed. And the premelting refining slag and the molten steel continuously react with the oxygen content in the molten steel in the VD vacuum process, so that the oxygen content in the steel is further reduced, and meanwhile, the prepared premelting refining slag continuously further adsorbs the generated Al2O3 inclusions. The method has the advantage that the purity of the bearing steel is further improved in the vacuum degassing process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of iron and steel metallurgy, and in particular relates to a composite deoxidation slagging agent for improving the purity of bearing steel in a vacuum process. Background Art

[0002] As an important component of engineering machinery, bearings have complex working environments and special service conditions that require bearing steel to have good fatigue life and quality stability, and an important quality indicator of bearing steel is purity control. Inclusions in steel have a crucial impact on the fatigue life of bearing steel. Inclusions destroy the continuity of the steel matrix, especially large-sized inclusions in bearing steel. Since bearing steel is aluminum-deoxidized steel, most of the inclusions are brittle inclusions. In addition, their large size will accelerate the fatigue peeling of the rolling surface and easily lead to a reduction in its fatigue life. Therefore, the control of large-sized inclusions has become a key factor affecting the further improvement of bearing steel quality.

[0003] The appearance of large-sized inclusions is more complicated, which is not only related to the purity control of steel, but also to the auxiliary refractory materials in contact during the smelting process, such as covering agents, ladle, tundish refractory, etc. In terms of purity control, bearing steel requires the oxygen content of the steel grade to be as low as possible. Therefore, in order to reduce the oxygen content in the steel, aluminum is usually used for deoxidation. The generated Al2O3 inclusions gather at the end of the stopper rod and inside the nozzle during the continuous casting process. When reaching a certain level, they will fall off and enter the molten steel to form large-sized inclusions. Therefore, it is necessary to reduce the generation of Al2O3 inclusions or remove the generated Al2O3 inclusions to the maximum extent on the basis of the oxygen content meeting the steel grade requirements.

[0004] The purity control of bearing steel is generally achieved by adding slag-forming agents such as lime and refined slag during the steel-making process or by slagging after the steel-making process. After slagging, slag-forming agents such as lime and refined slag are added to form refining process slag to adsorb Al2O3 inclusions in molten steel. As the smelting time increases, Al2O3 in the steel gradually transfers to the slag, achieving the metallurgical function of adsorbing inclusions in the molten steel. However, this process still has defects, that is, as the smelting time increases, Al2O3 in the refined slag gradually becomes saturated, the adsorption capacity decreases, and the purity of the molten steel cannot be further improved. Summary of the invention

[0005] The purpose of the present invention is to solve the problem that the existing slag-forming agents have limited effect on improving the purity of bearing steel, and to provide a composite deoxidizing slag-forming agent for improving the purity of bearing steel in a vacuum process, so as to further improve the purity of bearing steel in the vacuum degassing process.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: A composite deoxidizing slag-forming agent for improving the purity of bearing steel in a vacuum process, wherein the main components include metal aluminum wire, pre-melted refined slag and high-purity silicon carbide, wherein the weight proportions of the three materials are 10-12%, 63-70% and 20-25% respectively. The composite deoxidizing slag-forming agent takes pre-melted refined slag as the main body, and is added with 10-12% of metal aluminum wire and 20-25% of high-purity silicon carbide. The two continue to react with the oxygen content in molten steel during the VD vacuum process to further reduce the oxygen content in the steel, and at the same time, the added pre-melted refined slag continues to further adsorb the generated Al2O3 inclusions.

[0007] Furthermore, the main component of the metal aluminum wire is Al, and the Al content is not less than 99.3% to ensure the purity of the aluminum wire, the Ca content is not more than 0.05%, and the particle size is Φ5-10mm to ensure that the steel grade does not contain Ca elements to cause inclusion degeneration.

[0008] Furthermore, the pre-melted refined slag has a composition ratio of Al2O3, CaO, SiO2 and MgO, wherein, based on weight percentage, Al2O3: 20~25%, CaO: 60~65%, SiO2: 7~9%, MgO: 5~12%, and a particle size of 5~10 mm.

[0009] Furthermore, the main component of the high-purity silicon carbide is SiC, and SiC is not less than 90%, Ca is not more than 0.05%, and the particle size is Φ1-2mm, so as to ensure that the steel grade does not contain Ca elements to cause inclusion modification.

[0010] Furthermore, the composite deoxidizing slag-forming agent comprises 10% of metal aluminum wire, 70% of pre-melted refined slag, and 20% of high-purity silicon carbide.

[0011] Furthermore, the composite deoxidizing slag-forming agent comprises 12% of metal aluminum wire, 65% of pre-melted refined slag, and 23% of high-purity silicon carbide.

[0012] Furthermore, the composite deoxidizing slag-forming agent comprises 12% of metal aluminum wire, 63% of pre-melted refined slag, and 25% of high-purity silicon carbide.

[0013] In the technical solution of the present invention, a composite deoxidation slag-making agent is configured, wherein the pre-melted refined slag is prepared on the basis of studying the bearing steel slag system, and the activity of the component Al2O3 in the slag system is reduced by reducing the Al2O3 content, which is beneficial to [A1]+[O]=Al2O3, and the positive progress of the deoxidation reaction, thereby achieving the purpose of reducing the oxygen content, and is also beneficial to the migration of Al2O3 inclusions in the molten steel into the pre-melted refined slag, and then the Al2O3 inclusions in the molten steel can be further removed in the VD vacuum process, thereby further improving the purity of the steel. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is an analysis diagram of inclusion detection after using the slag-making agent obtained by the comparative example process in Example 1; Figure 2 This is an inclusion detection analysis diagram after using the composite deoxidizing slag-making agent of the present invention in Example 1; Figure 3 This is an inclusion detection analysis diagram after using the composite deoxidizing slag-making agent of the present invention in Example 2; Figure 4 This is an inclusion detection analysis diagram after using the composite deoxidizing slag-making agent of the present invention in Example 3. DETAILED DESCRIPTION Example 1

[0015] To make the present invention more clear, the composite deoxidation slag-forming agent for improving the purity of bearing steel in a vacuum process of the present invention is further described below in conjunction with the accompanying drawings. The specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0016] In this embodiment, a conventional process is first used as a comparative example, and the process path is: electric furnace-refining furnace-VD furnace-continuous casting.

[0017] (1) Electric furnace process: the tapping temperature is 1645°C, and 400 kg of lime and 600 kg of refined slag are added at the end of the tapping process; (2) Refining process: After smelting for 66 minutes, it enters the VD process; (3) VD process: vacuum degree 0.54 mbar, maintained for 20 minutes before breaking the vacuum, static stirring for 46 minutes before continuous casting; (4) Continuous casting process: 320*480 section, casting speed 0.51m / min.

[0018] After using slag forming agent in vacuum process, the inclusion detection analysis chart is as follows Figure 1 As shown, the inclusions are in the shape of strings, with the longest dimension being 38.28 μm.

[0019] In this embodiment 1, the process path includes electric furnace-refining furnace-VD furnace-continuous casting, which is characterized by: (1) Electric furnace process: The tapping temperature is 1638°C. At the end of the tapping process, 400 kg of lime and 600 kg of refined slag are added.

[0020] (2) Refining process: After smelting for 73 minutes, the VD process is entered. At the end of smelting, the refined slag is removed, and then 1 ton of the composite deoxidizing slag-making agent is added, with a ratio of 10% metal aluminum wire, 70% pre-melted refined slag, and 20% high-purity silicon carbide. The metal aluminum wire is Al, not less than 99.3% to ensure the purity of the aluminum wire, and Ca is not more than 0.05% to ensure that the steel grade does not contain Ca elements to cause inclusions to degenerate, and the particle size is Φ5~10mm; The pre-melted refined slag ratio is: based on weight percentage, including Al2O3: 20~25%, CaO: 60~65%, SiO2: 7~9%, MgO: 5~12%, and the particle size is 5~10mm. This pre-melted refined slag is based on the study of bearing steel slag system, and reduces the activity of Al2O3 in the slag system by reducing the Al2O3 content, which is beneficial to [A1]+[O]= Al2O3, the positive deoxidation reaction, thereby achieving the purpose of reducing the oxygen content, and is also beneficial to the migration of Al2O3 inclusions in the molten steel into the pre-melted refined slag. High-purity silicon carbide: SiC≥90%, Ca≤0.05%, to ensure that the steel grade does not contain Ca elements to cause inclusions to degenerate, 1~2mm.

[0021] (3) VD process: vacuum degree 0.49 mbar, maintained for 20 min before breaking the vacuum, static stirring for 55 min before continuous casting.

[0022] (4) Continuous casting process: 320*480 section, casting speed 0.51m / min.

[0023] After using the composite deoxidizing slag-making agent of Example 1 in the vacuum process, the inclusion detection analysis diagram is as follows: Figure 2 The inclusions are granular in shape, with the longest dimension being 5.41 μm. Example 2

[0024] In this embodiment 2, the process path includes electric furnace-refining furnace-VD furnace-continuous casting, which is characterized by: (1) Electric furnace process: The tapping temperature is 1636°C. At the end of the tapping process, 400 kg of lime and 600 kg of refined slag are added.

[0025] (2) Refining process: After 68 minutes of smelting, the VD process is entered. At the end of smelting, the refined slag is removed, and then 1 ton of the composite deoxidation slag-making agent is added, with a ratio of 12% metal aluminum wire, 65% pre-melted refined slag, and 23% high-purity silicon carbide. The metal aluminum wire is Al, not less than 99.3% to ensure the purity of the aluminum wire, and Ca is not more than 0.05% to ensure that the steel grade does not contain Ca elements to cause inclusions to degenerate, and the particle size is Φ5~10mm. The pre-melted refined slag ratio is: based on weight percentage, including Al2O3: 20~25%, CaO: 60~65%, SiO2: 7~9%, MgO: 5~12%, and the particle size is 5~10mm. By reducing the Al2O3 content, the activity of the Al2O3 component in the slag system is reduced, which is conducive to [A1] + [O] = Al2O3, the positive deoxidation reaction, thereby achieving the purpose of reducing the oxygen content, and is also conducive to the migration of Al2O3 inclusions in the molten steel to the pre-melted refined slag. High-purity silicon carbide: SiC ≥ 90%, Ca ≤ 0.05%, to ensure that the steel grade does not contain Ca elements to cause inclusions to degenerate, 1~2mm.

[0026] (3) VD process: vacuum degree 0.56 mbar, maintained for 20 min before breaking the vacuum, static stirring for 66 min before continuous casting.

[0027] (4) Continuous casting process: 320*480 section, casting speed 0.51m / min.

[0028] After using the composite deoxidizing slag-making agent of Example 2 in the vacuum process, the inclusion detection analysis diagram is as follows: Figure 3 The inclusions are granular in shape, with the longest dimension being 5.25 μm. Example 3

[0029] In this embodiment 3, the process path includes electric furnace-refining furnace-VD furnace-continuous casting, which is characterized by: (1) Electric furnace process: The tapping temperature is 1642°C. At the end of the tapping process, 400 kg of lime and 600 kg of refined slag are added.

[0030] (2) Refining process: After 65 minutes of smelting, the VD process is entered. At the end of smelting, the refined slag is removed, and then 1 ton of this deoxidizing slag-making agent is added, with a ratio of 12% metal aluminum wire, 63% pre-melted refined slag, and 25% high-purity silicon carbide. The metal aluminum wire is Al, not less than 99.3% to ensure the purity of the aluminum wire, and Ca is not more than 0.05% to ensure that the steel grade does not contain Ca elements to cause inclusions to degenerate, and the particle size is Φ5~10mm. The pre-melted refined slag ratio is: based on weight percentage, including Al2O3: 20~25%, CaO: 60~65%, SiO2: 7~9%, MgO: 5~12%, and the particle size is 5~10mm. By reducing the Al2O3 content, the activity of the Al2O3 component in the slag system is reduced, which is conducive to [A1] + [O] = Al2O3, the positive deoxidation reaction, thereby achieving the purpose of reducing the oxygen content, and is also conducive to the migration of Al2O3 inclusions in the molten steel to the pre-melted refined slag. High-purity silicon carbide: SiC ≥ 90%, Ca ≤ 0.05%, to ensure that the steel grade does not contain Ca elements to cause inclusions to degenerate, 1~2mm.

[0031] (3) VD process: vacuum degree 0.63 mbar, maintain for 20 minutes and then break the vacuum, stir for 45 minutes and then start continuous casting.

[0032] (4) Continuous casting process: 320*480 section, casting speed 0.51m / min.

[0033] After using the composite deoxidizing slag-making agent of Example 3 in the vacuum process, the inclusion detection analysis diagram is as follows: Figure 4 The inclusions are granular in shape, with the longest dimension being 3.58 μm.

[0034] Through the inclusion detection analysis comparison chart, that is, Figure 1 and Figures 2~4 By comparing the inclusions in the embodiment, it can be seen that the inclusions change from chain-like to granular, and the size is reduced from 38.28 μm to between 3 and 5.5 μm in the embodiment, which is a significant improvement.

[0035] In addition to the above embodiments, the present invention may also have other implementation modes. Any technical solution formed by equivalent replacement or equivalent transformation falls within the protection scope required by the present invention.

Claims

1. A composite deoxidizing slag-making agent for improving the purity of bearing steel in a vacuum process, characterized in that: The main components of the composite deoxidizing slag-forming agent include metal aluminum wire, pre-melted refined slag and high-purity silicon carbide. The weight proportions of the three materials are 10~12%, 63~70% and 20~25% respectively. The composite deoxidizing slag-forming agent takes pre-melted refined slag as the main body, and adds 10~12% of metal aluminum wire and 20~25% of high-purity silicon carbide. The two continue to react with the oxygen content in the molten steel during the VD vacuum process to further reduce the oxygen content in the steel. At the same time, the pre-melted refined slag continues to further adsorb the generated Al2O3 inclusions.

2. The composite deoxidation slag-making agent for improving the purity of bearing steel in a vacuum process according to claim 1, characterized in that: The main component of the metal aluminum wire is Al, and the Al content is not less than 99.3% to ensure the purity of the aluminum wire, the Ca content is not more than 0.05%, and the particle size is Φ5-10mm.

3. The composite deoxidation slag-making agent for improving the purity of bearing steel in a vacuum process according to claim 1 or 2, characterized in that: The pre-melted refined slag has a composition ratio of Al2O3, CaO, SiO2 and MgO, wherein, based on weight percentage, Al2O3: 20-25%, CaO: 60-65%, SiO2: 7-9%, MgO: 5-12%, and a particle size of 5-10 mm.

4. The composite deoxidation slag-making agent for improving the purity of bearing steel in a vacuum process according to claim 1 or 2, characterized in that: The main component of the high-purity silicon carbide is SiC, with SiC not less than 90%, Ca not more than 0.05%, and a particle size of Φ1-2mm.

5. The composite deoxidation slag-making agent for improving the purity of bearing steel in a vacuum process according to claim 1, characterized in that: The composite deoxidizing slag-forming agent has a ratio of 10% metal aluminum wire, 70% pre-melted refined slag, and 20% high-purity silicon carbide.

6. The composite deoxidation slag-making agent for improving the purity of bearing steel in a vacuum process according to claim 1, characterized in that: The composite deoxidizing slag-forming agent has a ratio of 12% metal aluminum wire, 65% pre-melted refined slag, and 23% high-purity silicon carbide.

7. The composite deoxidation slag-making agent for improving the purity of bearing steel in a vacuum process according to claim 1, characterized in that: The composite deoxidizing slag-forming agent has a ratio of 12% metal aluminum wire, 63% pre-melted refined slag, and 25% high-purity silicon carbide.